Ideology, Economic Policy, and Economic History: Cohen and DeLong's Concrete Economics - Field, Alexander J. (Journal of Economic Literature, 2017)
Stephen S. Cohen and J. Bradford DeLong view US economic policy extending up to 1980 as pragmatically fostering growth. This they interpret as the Hamiltonian tradition, and their intent is to rescue policy debate from the data- and logic-free quagmire into which they believe it has fallen. Following an introduction, section 2 of this essay describes methods and evidence that permit statements about the historical influence of ideological thinking more empirically grounded than those essayed by the authors. Section 3 examines specific aspects of their narrative. Section 4 considers what we mean by ideological thinking, and why it might be deleterious. (JEL D72, E61, L52, N41, N42)